(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article explores the historiography of research on the ethnic composition of the population of the Zarafshan Valley. It analyzes the main stages, directions, and methodological approaches that have shaped scholarly understanding of ethnic processes in the region from ancient times to the present. Special attention is paid to the works of domestic and foreign historians, ethnographers, and archaeologists who have studied the demographic and ethnocultural development of the Zarafshan Valley. The paper highlights how political, social, and cultural factors influenced the interpretation of ethnic history during different historical periods. The results of the study contribute to a deeper comprehension of the historiographical evolution of ethnic studies in Central Asia and provide a foundation for further interdisciplinary research.